P63 and Ki-67 expression in radicular cyst - Mohammed Amjed Alsaegh; Okba Mahmoud; Sudhir Rama Varma; Asok Mathew; Alaa Muayad Altaie; Shengrong Zhu (Journal of Oral Biology and Craniofacial Research)
Objectives: The aim of the current study was to identify the expression of P63 and its relation to odontogenic epithelial cell proliferation, severity of the inflammatory infiltrate and size of radicular cysts (RCs). Methods: In this retrospective cross-sectional study, 30 cases of paraffin-embedded RCs were randomly selected from the archive. P63 and Ki-67 expression was assessed by immunohistochemistry. Results: Epithelial P63 expression was absent in four (13.3%), weak in 10 (33.3%), and moderate in 16 (53.3%) cases. In the connective tissue wall of RC, P63 expression was absent in two (6.7%) cases, weak in 24 (80.0%) cases, and moderate in four (13.3%) cases. Ki-67 was found to be weakly expressed in 12 (40.0%) cases, moderately expressed in 13 (43.3%), and strongly expressed in five (16.7%) cases. No correlation was found between Ki-67 expression in odontogenic epithelium and P63 expression in the odontogenic epithelium (rho = 0.110, p = .563) or fibrous capsule (rho = 0.160, p = .399). Nevertheless, we found a positive correlation between Ki-67 expression in the odontogenic epithelium and the size of the RC (rho = 0.450, p = .013). The inflammatory infiltrate was negatively correlated with P63 expression in the odontogenic epithelium (rho = −0.428, p = .018), and with the size of cysts (rho = −0.728, p < .001). Conclusions: There is a high expression of P63 throughout the odontogenic epithelium and connective tissue capsule of the RC. P63 expression in the odontogenic epithelium is negatively correlated with the degree of the inflammatory infiltrate but not with epithelial cell proliferation or the size of the cyst.